Anti-corrosion process of chimney
By adding alumina nanoparticles to the titanium-steel composite plate of the chimney, combined with a high adhesion coating and intelligent monitoring system, the existing chimney corrosion protection technology has been solved, and more efficient , economical anti-corrosion effect and longer service life.
Patent Information
- Application Number
- CN202411542229.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The existing chimney corrosion protection technology is high and has weak corrosion resistance, limited adhesion of the coating, easy aging of lining materials, complex electrochemical protection equipment and high maintenance costs.
Using titanium-steel composite panels with alumina nanoparticles, the surface energy and adhesion are improved through plasma cleaning and nanocoating treatment, and the epoxy primer with high zinc content and a self-healing intermediate layer with microcapsule structures. Finally, High weather-resistant polymer topcoat is used and corrosion-proof effect is achieved through laser welding and intelligent monitoring systems.
It significantly improves the corrosion resistance of the chimney, extends the service life, reduces maintenance costs, and realizes real-time corrosion status monitoring and early warning through intelligent monitoring.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chimneys, in particular to an anti-corrosion process for chimneys. Background Art
[0002] A chimney is a tall vertical structure used to discharge flue gas, commonly used in industrial facilities such as power plants, factories and heating systems. The main function of a chimney is to discharge the flue gas produced by combustion into the atmosphere through natural or mechanical ventilation to avoid accumulation near the ground, thereby reducing harm to the environment and human health. Chimneys are subject to corrosion by various corrosive gases and chemicals during operation. If anti-corrosion treatment is not carried out, these substances will gradually corrode the inner wall of the chimney, causing structural damage and shortening the service life of the chimney. Corrosion can cause cracks or holes in the chimney wall, which in turn causes flue gas leakage. This not only affects the normal function of the chimney, but may also cause environmental pollution and safety hazards. Chimneys damaged by corrosion are structurally unstable and are prone to collapse or partial collapse under extreme weather conditions, threatening the safety of surrounding personnel and facilities. Preventive anti-corrosion treatment can greatly reduce the cost of later repairs and replacements, and reduce frequent shutdowns and maintenance caused by corrosion. Effective anti-corrosion measures can ensure the normal operation of the chimney's emission system, reduce the leakage of harmful substances, and protect the environment.
[0003] In the prior art, chimney corrosion protection is usually achieved through coating corrosion protection, lining corrosion protection, and electrochemical protection. Coating corrosion protection uses epoxy resin coating as an anti-corrosion material, and the coating usually includes primer, intermediate paint and topcoat. Or polyurethane is used as a coating material, which has good chemical resistance and mechanical properties. Or an inorganic zinc-rich primer with a high zinc content is used to provide cathodic protection. Lining corrosion protection uses glass fiber reinforced plastic (FRP) material as the chimney lining, which has excellent corrosion resistance. Or an acid- and alkali-resistant rubber lining is laid on the inner wall of the chimney to prevent flue gas corrosion. Electrochemical protection uses electric current or sacrificial anode to make the metal surface of the chimney a cathode, thereby preventing corrosion. Or the metal surface of the chimney is passivated by an external current to reduce the corrosion rate. In these technologies, the coating corrosion protection coating has limited adhesion and is prone to peeling. General coatings cannot self-repair after being damaged and require regular maintenance. Lining corrosion protection such as glass fiber reinforced plastic and rubber lining is complex to construct, with high cost and long construction period. Once the lining is damaged, it is difficult to repair and needs to be replaced as a whole, with high maintenance cost. In addition, the lining material is prone to aging and has a limited service life in high temperature and chemical environments. Electrochemical protection requires complex power supply systems and control equipment, with high installation and maintenance costs. The protection effect is greatly affected by environmental factors, and it is difficult to ensure uniform protection in complex environments.
[0004] Therefore, the present invention proposes an anti-corrosion process for a chimney to solve the above-mentioned problems. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention provides an anti-corrosion process for a chimney, which solves the problems of high cost and weak corrosion resistance in the prior art.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A chimney anti-corrosion process specifically includes the following steps:
[0007] S1. Steel preparation
[0008] Use high-quality titanium-steel composite plates, and add alumina nanoparticles to the titanium-steel composite plates to achieve internal modification. In this process, mixing equipment is required to ensure the uniform distribution of nanoparticles in the substrate;
[0009] S2. Steel Processing
[0010] Use plasma cleaning technology to thoroughly remove oil and impurities on the steel surface, and spray a layer of nano coating on the surface of the titanium-steel composite plate to further increase the surface energy and enhance the bonding strength between the coating and the substrate;
[0011] S3. Base coating
[0012] Choose an epoxy primer with a high zinc content to provide an excellent anti-corrosion barrier, and use airless spray equipment to evenly apply the primer, ensuring a coating thickness of 40-60 microns;
[0013] S4. Intermediate layer construction
[0014] Apply a self-repairing middle layer containing a microcapsule structure to ensure the self-repairing function of the anti-corrosion layer, and use spraying equipment to ensure that the middle layer coating is uniform and defect-free;
[0015] S5. Surface protection
[0016] The final coat of paint uses a highly weather-resistant polymer topcoat to prevent erosion by ultraviolet rays and other environmental factors. Multi-layer spraying technology is used to ensure the thickness and uniformity of each layer of coating, and infrared heating equipment is used to accelerate the coating curing process.
[0017] S6. Welding and installation
[0018] Finely polish and clean the welding parts, use protective gas to cover the welding area to prevent oxidation, use laser welding technology to achieve welding, and after welding, perform ultrasonic flaw detection in the weld area to ensure there are no defects. Perform secondary coating on the weld to ensure the consistency of the anti-corrosion effect;
[0019] S7. Intelligent monitoring
[0020] A sensor network is installed in the inner tube of the chimney to monitor temperature, humidity and corrosion in real time. The sensor data is transmitted wirelessly to the monitoring center to achieve real-time monitoring and early warning.
[0021] Preferably, in the steel preparation step S1, the particle size of the aluminum oxide nanoparticles is 20-50 nm, and the addition ratio is 1.5 wt%.
[0022] Preferably, in the steel material treatment step S2, the nano coating is SiO2 nanoparticles and a binder, with a particle size of 10-20 nm and a concentration of 2 wt%.
[0023] Preferably, the coating thickness of the self-repairing intermediate layer coating containing a microcapsule structure in the intermediate layer construction of step S4 is 100-150 microns.
[0024] Preferably, the thickness of the coating in the surface protection in step S5 is 20-30 microns per layer, and the total thickness is 60-90 microns.
[0025] Preferably, in step S6, the welding and installation are performed by using argon shielding gas to cover the welding area.
[0026] Preferably, the sensors installed in the intelligent monitoring in step S7 include temperature sensors, humidity sensors, pH sensors, corrosion rate sensors, and electrochemical sensors.
[0027] The present invention provides a chimney anti-corrosion process, which has the following beneficial effects:
[0028] The present invention provides an anti-corrosion process for a chimney. The present invention adds aluminum oxide nanoparticles to a titanium-steel composite plate to enhance the wear resistance and corrosion resistance of the material, uses plasma cleaning technology to ensure surface cleanliness and improve coating adhesion, uses a self-repairing intermediate layer coating containing a microcapsule structure, has a self-repairing function, and extends the service life of the coating, uses a highly weather-resistant polymer topcoat to prevent erosion by ultraviolet rays and environmental factors and ensure long-term durability, uses laser welding with high welding precision, a small heat-affected zone, and excellent welding quality, uses a protective gas covering during welding to prevent oxidation and improve welding quality, installs a sensor network to monitor the corrosion state of the chimney in real time, and provides timely warning and maintenance. The present invention has significant improvements in material selection, coating process, welding technology, and intelligent monitoring, and can effectively improve the anti-corrosion performance of the chimney, extend its service life, and reduce maintenance costs. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] The embodiment of the present invention provides a chimney anti-corrosion process, which specifically includes the following steps:
[0031] S1. Steel preparation
[0032] Use high-quality titanium-steel composite plates, and add alumina nanoparticles to the titanium-steel composite plates to achieve internal modification. In this process, mixing equipment is required to ensure the uniform distribution of nanoparticles in the substrate.
[0033] The specific steps are:
[0034] 1. Titanium-steel composite plate selection
[0035] Material selection: Use high-quality titanium-steel composite plates, the specific specifications are:
[0036] Titanium layer thickness: 0.5mm
[0037] Steel layer thickness: 5mm
[0038] Total thickness: 5.5mm
[0039] Titanium layer material: TA2 (industrial pure titanium)
[0040] Steel layer material: Q345R (steel plate for pressure vessels)
[0041] 2. Addition of Nanoparticles
[0042] Nanoparticle Type: Alumina Nanoparticles (Al2O3)
[0043] Particle size: 20-50nm
[0044] Addition ratio: 1.5wt% (weight percentage)
[0045] 3. Mixing process
[0046] Equipment: High-precision mixing equipment (such as ultrasonic disperser or high shear mixer)
[0047] Mixing parameters:
[0048] Mixing time: 30 minutes
[0049] Mixing temperature: 25℃ (room temperature)
[0050] Speed: 3000rpm (if using high shear mixer)
[0051] Process flow:
[0052] Nanoparticle pretreatment: The aluminum oxide nanoparticles are surface modified to improve their dispersibility in the titanium-steel composite plate. Common methods include the use of coupling agents or plasma treatment.
[0053] Preliminary mixing: Preliminary mixing of the titanium-steel composite plate material with the pretreated alumina nanoparticles to ensure that the nanoparticles are evenly distributed on the surface of the material.
[0054] High-precision mixing: The preliminarily mixed materials are placed in a high-precision mixing device for secondary mixing to ensure uniform distribution of the nanoparticles within the substrate.
[0055] 4. Internal modification effect verification
[0056] Methods: Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) were used to analyze the microstructure and composition distribution of the materials.
[0057] Result criteria: Ensure that the aluminum oxide nanoparticles are evenly distributed in the titanium-steel composite plate matrix without obvious aggregation.
[0058] Through the above steps, the titanium-steel composite plate has completed internal modification with the addition of nanoparticles, which improves the wear resistance and corrosion resistance of the material and lays a solid foundation for the subsequent anti-corrosion coating construction.
[0059] S2. Steel Processing
[0060] Plasma cleaning technology is used to thoroughly remove oil and impurities on the surface of the steel, and a layer of nano-coating is sprayed on the surface of the titanium-steel composite plate to further increase the surface energy and enhance the bonding strength between the coating and the substrate.
[0061] The specific steps are:
[0062] 1. Preliminary cleaning
[0063] Technical method: plasma cleaning technology
[0064] Purpose: To thoroughly remove oil stains, oxide layers and impurities on the surface of steel to ensure surface cleanliness.
[0065] Equipment: Plasma cleaning equipment
[0066] Parameter settings:
[0067] Power: 100W
[0068] Processing time: 10 minutes
[0069] Gas type: Argon or argon mixed with oxygen
[0070] Gas flow rate: 50sccm (standard cubic centimeters per minute)
[0071] Effect detection: Surface cleanliness was analyzed using contact angle measurement and X-ray photoelectron spectroscopy (XPS).
[0072] Standard: The surface contact angle is less than 10° and there is no obvious contamination peak in XPS detection.
[0073] 2. Surface coating
[0074] Material: Nano coating material
[0075] Main ingredients: SiO2 nanoparticles and binder
[0076] Particle size: 10-20nm
[0077] Concentration: 2wt%
[0078] Spraying process:
[0079] Equipment: Nano spraying equipment
[0080] Spraying method: electrostatic spraying
[0081] Spraying parameters:
[0082] Voltage: 20kV
[0083] Spraying distance: 20cm
[0084] Spraying speed: 30cm / min
[0085] Coating thickness: 50-100nm
[0086] Coating curing:
[0087] Method: Infrared heating curing
[0088] Temperature: 120℃
[0089] Duration: 30 minutes
[0090] Effect detection:
[0091] Methods: Scanning electron microscopy (SEM) and atomic force microscopy (AFM) were used to analyze the surface morphology and coating thickness.
[0092] Standard: The coating is uniform and defect-free, with a thickness between 50-100nm.
[0093] Detailed implementation steps
[0094] Plasma cleaning
[0095] Turn on the plasma cleaning equipment, set the gas flow and power, and start the cleaning process.
[0096] The titanium-steel composite plates are evenly placed in the processing chamber to ensure that each plate is evenly exposed to the plasma.
[0097] After cleaning, take out the plate and immediately measure the surface contact angle to ensure the surface is clean.
[0098] Nano coating spraying
[0099] SiO2 nanoparticles were dispersed in a solvent at a ratio of 2 wt % and mixed using an ultrasonic disperser for 30 minutes to ensure uniform dispersion.
[0100] The electrostatic spraying equipment is loaded and the titanium-steel composite plate is fixed on a rotating table to ensure uniform spraying.
[0101] Set the spraying voltage and spraying distance, start the electrostatic spraying equipment, and spray the nano coating.
[0102] After spraying, the coated titanium-steel composite plate is placed in an infrared heating device for curing, and the curing temperature and time are set.
[0103] Effect detection
[0104] Use SEM and AFM to inspect the surface morphology and thickness of the coating to ensure that the coating is uniform and defect-free.
[0105] Record the test results to ensure that each titanium-steel composite plate meets the standard requirements.
[0106] Through the above detailed steps, it is ensured that the titanium-steel composite plate achieves the best effect during the cleaning and coating process, providing a high-quality substrate for the subsequent coating process.
[0107] S3. Base coating
[0108] Choose an epoxy primer with a high zinc content to provide an excellent barrier against corrosion and use airless spray equipment to apply the primer evenly, ensuring a coating thickness of 40-60 microns.
[0109] The specific steps are:
[0110] 1. Primer selection
[0111] Material: Epoxy primer with high zinc content
[0112] Zinc content: 60%wt
[0113] Main ingredients: epoxy resin, zinc powder, curing agent
[0114] Brand example: Sherwin-Williams Zinc Clad
[0115] 2. Primer coating
[0116] Equipment: Airless spray equipment
[0117] Spraying parameters:
[0118] Nozzle diameter: 0.019-0.021 inches
[0119] Spraying pressure: 2500-3000psi
[0120] Spraying distance: 30-50cm
[0121] Coating thickness: 40-60 microns
[0122] Process flow:
[0123] Surface pretreatment: Make sure the surface is free of dust, oil and dry.
[0124] Primer spraying: Spray the primer evenly to ensure that the coating thickness meets the requirements.
[0125] Curing: Curing at room temperature for 24 hours to ensure that the coating is fully cured.
[0126] 3. Effect detection
[0127] Method: Use a coating thickness gauge to check the thickness to ensure it meets the standards.
[0128] Standard: Uniform coating thickness, no missing coating, thickness 40-60 microns.
[0129] S4. Intermediate layer construction
[0130] A self-repairing middle layer containing a microcapsule structure is applied to ensure the self-repairing function of the anti-corrosion layer, and spraying equipment is used to ensure that the middle layer coating is uniform and defect-free.
[0131] The specific steps are:
[0132] 1. Middle layer selection
[0133] Material: Self-healing intermediate layer coating containing microcapsule structure
[0134] Main ingredients: polyurethane resin, microcapsules, fillers
[0135] Brand example: 3M Scotch-Weld Epoxy Adhesive DP420
[0136] 2. Middle layer coating
[0137] Equipment: Spraying equipment
[0138] Spraying parameters:
[0139] Nozzle diameter: 0.015-0.017 inches
[0140] Spraying pressure: 1500-2000psi
[0141] Spraying distance: 30-50cm
[0142] Coating thickness: 100-150 microns
[0143] Process flow:
[0144] Surface preparation: 24 hours after basecoating, ensure the surface is dry and clean.
[0145] Intermediate layer spraying: spray the intermediate layer of paint evenly to ensure that the coating is free of defects.
[0146] Curing: Curing at room temperature for 24 hours, or heating curing (60℃, 2 hours).
[0147] 3. Effect detection
[0148] Method: Coating thickness gauge and visual inspection.
[0149] Standard: Uniform coating thickness, no bubbles and sagging, thickness 100-150 microns.
[0150] S5. Surface protection
[0151] The final coat of paint uses a highly weather-resistant polymer topcoat to prevent erosion by UV rays and other environmental factors. Multi-layer spraying technology is used to ensure the thickness and uniformity of each layer of coating, and infrared heating equipment is used to accelerate the coating curing process.
[0152] The specific steps are:
[0153] 1. Surface coating selection
[0154] Material: Highly weather-resistant polymer topcoat
[0155] Main ingredients: fluorocarbon resin, UV stabilizer, pigment
[0156] Brand example: PPG Duranar
[0157] 2. Surface coating
[0158] Equipment: Multi-layer spraying equipment
[0159] Spraying parameters:
[0160] Nozzle diameter: 0.011-0.013 inches
[0161] Spraying pressure: 2000-2500psi
[0162] Spraying distance: 30-50cm
[0163] Coating thickness: 20-30 microns per layer, total thickness 60-90 microns
[0164] Process flow:
[0165] Surface preparation: After the interlayer has cured, ensure the surface is dry and clean.
[0166] Topcoat spraying: Spray in multiple layers, allowing each layer to dry slightly (20 minutes) before spraying the next layer.
[0167] Curing: Use infrared heating equipment to accelerate curing, the curing temperature for each layer is 80°C and the curing time is 1 hour.
[0168] 3. Effect detection
[0169] Methods: Coating thickness gauge, UV weathering test and visual inspection.
[0170] Standard: Uniform coating thickness, no bubbles and sagging, total thickness 60-90 microns. Passed UV weathering test, no obvious fading or chalking.
[0171] S6. Welding and installation
[0172] The welding parts are finely polished and cleaned, and the welding area is covered with protective gas to prevent oxidation. Laser welding technology is used to achieve welding. After welding, ultrasonic flaw detection is performed in the weld area to ensure that there are no defects. The weld is treated with a secondary coating to ensure the consistency of the anti-corrosion effect.
[0173] The specific steps are:
[0174] 1. Welding preparation
[0175] Surface treatment: Finely polish and clean the welding parts to ensure they are free of oil, rust and impurities.
[0176] Polishing equipment: electric polishing machine
[0177] Polishing material: 320 grit sandpaper
[0178] Cleaning agent: anhydrous ethanol or acetone
[0179] 2. Protective gas coverage
[0180] Protective gas: Argon (purity 99.99%)
[0181] Gas flow rate: 15-20L / min
[0182] Equipment: Protective gas blanketing device
[0183] Setup: Place a protective shield over the welding area to ensure argon coverage during welding to prevent oxidation.
[0184] 3. Welding
[0185] Welding technology: laser welding
[0186] Equipment: Fiber laser welding machine
[0187] Welding parameters:
[0188] Laser power: 3000W
[0189] Welding speed: 500mm / min
[0190] Focus position: weldment surface
[0191] Protective gas flow rate: 15L / min (argon)
[0192] Process flow:
[0193] Fix the workpiece: fix the welding part of the titanium-steel composite plate on the welding platform.
[0194] Welding: Start the laser welding machine and perform welding according to the set parameters.
[0195] Protection: Always keep argon gas cover during welding to prevent oxidation of the welding area.
[0196] 4. Weld inspection
[0197] Method: Ultrasonic flaw detection
[0198] Equipment: Ultrasonic flaw detector
[0199] Detection parameters:
[0200] Frequency: 5MHz
[0201] Probe diameter: 10mm
[0202] Process flow:
[0203] Preparation for testing: Move the flaw detector probe over the weld area to ensure full coverage.
[0204] Inspection: Turn on the flaw detector, conduct weld inspection, and record the inspection data.
[0205] Result analysis: Analyze the test data to ensure that the weld is free of defects such as cracks and pores.
[0206] Standard: No defects such as cracks, pores, and lack of fusion. The weld quality complies with GB / T 11345 standard.
[0207] 5. Secondary coating treatment
[0208] Materials: Same nano coating material and highly weather-resistant polymer topcoat
[0209] Coating thickness:
[0210] Primer: 40-60 microns
[0211] Middle layer: 100-150 microns
[0212] Topcoat: 20-30 microns per layer, total thickness 60-90 microns
[0213] Process flow:
[0214] Surface preparation: Clean and polish the weld area to ensure it is free of oil and oxides.
[0215] Primer spraying: Spray the primer evenly, ensuring a thickness of 40-60 microns.
[0216] Intermediate layer spraying: Evenly spray the self-repairing intermediate layer to ensure a thickness of 100-150 microns.
[0217] Topcoat spraying: Multi-layer spray topcoat, total thickness 60-90 microns.
[0218] Curing: Use infrared heating equipment for curing, the curing temperature for each layer is 80℃, and the curing time is 1 hour.
[0219] 6. Effect detection
[0220] Methods: Coating thickness gauge, ultrasonic flaw detector and visual inspection.
[0221] Standard: The coating thickness is uniform and free of defects, the total thickness meets the requirements, and there are no defects in the weld area.
[0222] Through the above detailed steps, the quality and anti-corrosion effect of each link in the welding and installation process are ensured, thereby ensuring the overall anti-corrosion performance and long-term service life of the chimney.
[0223] S7. Intelligent monitoring
[0224] A sensor network is installed in the inner tube of the chimney to monitor temperature, humidity and corrosion in real time. The sensor data is transmitted wirelessly to the monitoring center to achieve real-time monitoring and early warning.
[0225] The specific steps are:
[0226] 1. Overview of Intelligent Monitoring System
[0227] Objective: To monitor the corrosion status of the chimney surface and internal environment in real time, and to detect and prevent corrosion problems in a timely manner.
[0228] Monitoring content: temperature, humidity, pH value, corrosion rate, electrochemical parameters, etc.
[0229] 2. Sensor selection
[0230] Temperature Sensor
[0231] Model: PT100 platinum resistance temperature sensor
[0232] Measuring range: -50℃ to +250℃
[0233] Accuracy: ±0.1℃
[0234] Humidity Sensor
[0235] Model: Honeywell HIH-4000 Series
[0236] Measuring range: 0% RH to 100% RH
[0237] Accuracy: ±2% RH
[0238] pH Sensor
[0239] Model: Atlas Scientific EZO-pH Sensor
[0240] Measuring range: 0 to 14 pH
[0241] Accuracy: ±0.02pH
[0242] Corrosion Rate Sensor
[0243] Model: Corrosometer
[0244] Measuring principle: Resistance change method
[0245] Measuring range: 0 to 10 mpy (millions per year)
[0246] Electrochemical Sensors
[0247] Model: Gamry Reference 600+
[0248] Measurement parameters: open circuit potential, polarization resistance, electrochemical impedance
[0249] 3. Data collection and transmission
[0250] Data acquisition module
[0251] Model: National Instruments NI-9219
[0252] Number of channels: 4 channels
[0253] Resolution: 24 bits
[0254] Sampling rate: 100S / s
[0255] Data Transfer
[0256] Communication protocol: LoRa (long-distance wireless communication)
[0257] Data transfer rate: 0.3kbps to 50kbps
[0258] Transmission distance: up to 10 km
[0259] Gateway device: LoRa Gateway (model: RAK7249)
[0260] 4. Monitoring system installation
[0261] Installation location: The sensors are evenly distributed on the inner and outer surfaces of the chimney and key welding areas.
[0262] Installation method: magnetic fixation and anti-corrosion glue fixation.
[0263] Installation steps:
[0264] Determine the installation point: select the monitoring point for temperature, humidity, pH value, corrosion rate, and electrochemical parameters.
[0265] Fix the sensor: Use magnets to fix the sensor, making sure it is close to the surface; use anti-corrosion glue to fix areas that cannot be fixed magnetically.
[0266] Connect the data acquisition module: Connect the sensor to the NI-9219 data acquisition module.
[0267] Set up LoRa communication: Install the LoRa communication module, configure data transmission parameters, and ensure signal coverage.
[0268] 5. Data monitoring and analysis
[0269] Data storage: Use cloud storage platforms (such as AWS IoT Core) for data storage and management.
[0270] Real-time monitoring: Real-time monitoring and display of data is achieved through data visualization platforms (such as Grafana).
[0271] Alarm system: Set up a threshold alarm system. When the temperature, humidity, pH value, corrosion rate, and electrochemical parameters exceed the set range, the alarm is triggered and a notification (SMS or email) is sent.
[0272] Data Analysis:
[0273] Periodic analysis: Generate reports regularly to analyze the changing trends of various parameters.
[0274] Fault early warning: Predict potential corrosion risks through data modeling and machine learning algorithms.
[0275] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A chimney anti-corrosion process, characterized in that: The specific steps include: S1. Steel preparation Use high-quality titanium-steel composite plates, and add aluminum oxide nanoparticles to the titanium-steel composite plates to achieve internal modification. In this process, mixing equipment is required to ensure the uniform distribution of nanoparticles in the substrate; S2. Steel Processing Use plasma cleaning technology to thoroughly remove oil and impurities on the steel surface, and spray a layer of nano coating on the surface of the titanium-steel composite plate to further increase the surface energy and enhance the bonding strength between the coating and the substrate; S3. Base coating Choose an epoxy primer with a high zinc content to provide an excellent anti-corrosion barrier, and use airless spray equipment to evenly apply the primer, ensuring a coating thickness of 40-60 microns; S4. Intermediate layer construction Apply a self-repairing middle layer containing a microcapsule structure to ensure the self-repairing function of the anti-corrosion layer, and use spraying equipment to ensure that the middle layer coating is uniform and defect-free; S5. Surface protection The final coat of paint uses a highly weather-resistant polymer topcoat to prevent erosion by ultraviolet rays and other environmental factors. Multi-layer spraying technology is used to ensure the thickness and uniformity of each layer of coating, and infrared heating equipment is used to accelerate the coating curing process. S6. Welding and installation Finely polish and clean the welding parts, use protective gas to cover the welding area to prevent oxidation, use laser welding technology to achieve welding, and after welding, perform ultrasonic flaw detection in the weld area to ensure there are no defects. Perform secondary coating on the weld to ensure the consistency of the anti-corrosion effect; S7. Intelligent monitoring A sensor network is installed in the inner tube of the chimney to monitor temperature, humidity and corrosion in real time. The sensor data is transmitted wirelessly to the monitoring center to achieve real-time monitoring and early warning.
2. The anti-corrosion process for a chimney according to claim 1, characterized in that: In the steel preparation step S1, the particle size of the aluminum oxide nanoparticles is 20-50 nm, and the addition ratio is 1.5 wt%.
3. The anti-corrosion process for a chimney according to claim 1, characterized in that: In the steel material treatment step S2, the nano coating comprises SiO2 nanoparticles and a binder, with a particle size of 10-20 nm and a concentration of 2 wt%.
4. The anti-corrosion process for a chimney according to claim 1, characterized in that: The coating thickness of the self-repairing intermediate layer coating containing a microcapsule structure in the intermediate layer construction of step S4 is 100-150 microns.
5. The anti-corrosion process for a chimney according to claim 1, characterized in that: In the step S5, the thickness of the coating in the surface protection is 20-30 microns per layer, and the total thickness is 60-90 microns.
6. The anti-corrosion process for a chimney according to claim 1, characterized in that: In the step S6, the welding and installation are performed by covering the welding area with argon protective gas.
7. The anti-corrosion process for a chimney according to claim 1, characterized in that: The sensors installed in the intelligent monitoring of step S7 include temperature sensors, humidity sensors, pH sensors, corrosion rate sensors, and electrochemical sensors.